(untitled) (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2022)
Business leadership by women is a special challenge in Kosovo, as, until the 90s, it was almost taboo. In this context, from 2000 onwards in Kosovo, there have been many businesses run by businesswomen, which is a great contribution to the emancipation of modern society. Women’s businesses in Kosovo face many challenges and barriers; thus, this research study aims to address this issue. The purpose of this study is to investigate and find out the challenges and obstacles faced by women entrepreneurs in their business activities. The empirical investigation will be conducted using a questionnaire-based survey of 213 women entrepreneurs in the Republic of Kosovo in 2021. The data were collected through a questionnaire with closed questions. A total of 213 female entrepreneurs from all regions of Kosovo participated in the research. Based on the results achieved through Factorial analysis, one of the main challenging factors of women-led businesses are the instability of doing business that is directly related to high taxes and high loans, bureaucracy, lack of support, lack of modern technology, and access to the market, with statistical significance at 5% level of significance. Business leadership by women needs to be supported by the Government by enabling lower interest rates and granted loans, investments in terms of staff and products, as well as technology modernization.